The role of self-construal in moderating the advertising repetition effect: evidence from Korea. Issue 2 (3rd March 2016) - Lee, Byung-Kwan; Lee, YouNa
ABSTRACT: This study explored the role of self-construal in moderating the effect of same- and varied-ad repetition on consumer response to advertising and brand on the basis of self-construal and encoding variability theory. In the study, subjects primed with independent or interdependent self-construal were exposed to either the same or varied ads. Findings indicate that, for foreground information in ad, independent self-construal subjects elicited more than interdependent self-construal subjects in same-ad repetition whereas there was no difference between independent and interdependent self-construal subjects in varied-ad repetition. However, for background information, interdependent self-construal subjects performed better than independent self-construal subjects in both same- and varied-ad repetition. In the case of brand recall, in varied-ad repetition, interdependent self-construal subjects recalled better than independent self-construal subjects did, whereas there was no difference between interdependent and independent self-construal subjects in same-ad repetition. It was also found interdependent self-construal subjects evaluated the target brand more positively than independent self-construal subjects did in varied-ad repetition. However, there was no difference in brand attitude between independent and interdependent subjects in same-ad repetition.